Learning from a distance during a pandemic outbreak: Factors affecting students' acceptance of distance learning during school closures due to COVID-19 - Bobby Ardiansyahmiraja; Reny Nadlifatin; Satria Fadil Persada; Yogi Tri Prasetyo; A.A.N Perwira Redi (Je-LKS: Journal of E-Learning and Knowledge Society, 2021)
Distance learning has become the only solution for learning in the current Covid-19 pandemic outbreak. A more straightforward form of distance learning with the utilization of telepresence and cloud-based productivity tools was apparent in many institutions. The present study investigated this phenomenon and ask, “What factors affect students’ acceptance of distance learning during school closures due to COVID-19?”. An extended Unified Theory of Acceptance and Use of Technology was employed to answer the research question, with 156 students participating in the study. The result revealed that Effort Expectancy (EE) has the biggest effect on students’ acceptance of distance learning during school closures (β=0.372, p<0.001). Additionally, the extended variable of Socia l Presence (SP) was also showing great effects on students' acceptance (β=0.296, p<0.001). However, one of the UTAUT constructs, Facilitating Conditions, was found to have no effect on students' acceptance. Practical implications for schools and distance learning program managers were discussed to provide insight on improving a distance learning program. This study contributes to the body of knowledge on learning technologies as well as on how society, especially in the educational sector, should continue despite the current pandemic crisis.